CADD-21. PROTEASOME INHIBITION IS A TARGETED THERAPY FOR PTEN-DEFICIENT GLIOBLASTOMAS. (5th November 2018) - Benitez, Jorge; Finlay, Darren; Ma, Jianhui; Koga, Tomoyuki; Vuori, Kristiina; Furnari, Frank
Abstract: One of the most common genetic alterations in glioblastoma (30–40%) occurs in the PTEN (phosphatase and tensin homolog) tumor suppressor gene, where loss of function has been mechanistically linked to increased tumor cell invasion, and to a lack of radio- and chemo-therapy response. To identify new drug compounds that target PTEN-deficient brain tumors we performed a high throughput drug screen using patient-derived GBM spheres and found that PTEN-deficient samples were highly sensitive to proteasome inhibition. We confirmed this sensitivity in GBM spheres and iNPCs (inducible Neuronal Progenitor Cells) by genetically over-expressing or deleting PTEN, where PTEN over-expression decreased and PTEN-deletion increased sensitivity to the drug, respectively. Additionally, proteasome inhibition specifically suppressed tumor growth in mice of orthotopically engrafted human glioblastoma samples. Mechanistically, we determined that PTEN-deficient cells are more sensitive to proteasome inhibition due to an increase in protein synthesis rate and loss of autophagy activity associated with activation of the PI3K/mTOR pathway. This study reveals that proteasome inhibition is a targeted-therapeutic strategy for PTEN-deficient brain cancer.